Hetero‐Polycrystalline Membranes with Narrow and Rigid Pores for Molecular Sieving. Issue 3 (20th November 2022) - Li, Wanbin; Su, Pengcheng; Tang, Huiyu; Lin, Yanshan; Yu, Yanqing
Abstract: Molecular sieving membranes have great potential for energy‐saving separations, but they suffer from permeability‐selectivity trade‐off limitation. In this report, simultaneous hetero‐crystallization and hetero‐linker coordination of metal–organic framework (MOF) hollow fiber membranes through one‐pot synthesis for precise gas separation is reported. It is found that the hetero‐polycrystalline membranes consist of 2D and 3D MOF phases and are defect‐free and roughly orientated, hetero‐linker exchange of 3D phase by larger geometric ones can narrow transport pathway, and framework rigidification occurs and thus fixes MOF channels. The prepared membranes are robust and reproducible, and exhibit substantially improved performance, with H2 /CO2, H2 /N2, and H2 /CH4 selectivities up to 361, 482, and 541, respectively, accompanied by high H2 permeance over 1100 gas permeation units, which can easily outclass trade‐off upper bounds of state‐of‐the‐art membranes. Abstract : Metal‐organic framework (MOF) membranes are prepared by simultaneously hetero‐crystallization and hetero‐coordination from one‐pot synthesis. The hetero‐polycrystalline MOF hollow fiber membranes consist of 2D and 3D MOF phases, are defect‐free and roughly orientated, have narrowed and rigid transport pathways, and show high H2 permeance and one to two orders of magnitude higher selectivity than conventional membranes.